Respuesta :
Answer:
y=3 - 2x/-9
Step-by-step explanation:
-9y=-27-2x
y=-27-2x/-9
y=-27/-9 - 2x/-9
y=3 - 2x/-9
Answer: y = 3 + 2x/9
Step-by-step explanation: All we need to do for this equation is to get any variables/digits other than y to the right side of the equation. To do so, we must first move 2x to the other side of the equal sign. Once a number switches sides, its sign changes. So, our equation would now look like this:
-9y = -27 - 2x
Now, we need to separate the -9 from the y, so we can divide both sides of the equation by -9.
-9y/-9 = -27/-9 - 2x/-9
y = 3 + 2x/9
Hope this was helpful! Let me know if you have any further questions. :)